A note on a conjecture on consistent cycles - Miklavič, Štefko (Ars mathematica contemporanea, 2013)
Let ?$Γ$? denote a finite digraph and let ?$G$? be a subgroup of its automorphism group. A directed cycle ?$\vec{C}$? of? $Γ$? is called ?$G$?-consistent whenever there is an element of ?$G$? whose restriction to? $\vec{C}$? is the 1-step rotation of ?$\vec{C}$?. In this short note we provea conjecture on ?$G$?-consistent directed cycles stated by Steve Wilson.
Keywords: consistent directed cycles; digraphs; graph theory; teorija grafov